2000
DOI: 10.1038/sj.onc.1203429
|View full text |Cite
|
Sign up to set email alerts
|

Survivin initiates procaspase 3/p21 complex formation as a result of interaction with Cdk4 to resist Fas-mediated cell death

Abstract: Caspase 3 is an essential death factor for the Fasmediated cell death, and its inactivation in cells is initiated by an interaction with p21 on mitochondria or with IAP family member ILP. Survivin is also a member of IAP family and is speci®cally expressed during embryogenesis and in tumor cells and suppresses cell death signaling. In our current study, we demonstrated that Survivin translocation into the nucleus is dependent on Fas stimulation and cell proliferation. Survivin also interacts with the cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
148
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(158 citation statements)
references
References 37 publications
5
148
1
4
Order By: Relevance
“…Our study has confirmed that EBV LMP1 could cause the G 1 /S check point disorder and accelerate G 1 -S transition in NPC cells [15,16]. G 1 /S check point is a critical restriction point co-regulated by Cyclin D and CDK4.…”
Section: Initiation Of Survivin/ Cdk4 Complex Formation In the Nucleisupporting
confidence: 74%
See 1 more Smart Citation
“…Our study has confirmed that EBV LMP1 could cause the G 1 /S check point disorder and accelerate G 1 -S transition in NPC cells [15,16]. G 1 /S check point is a critical restriction point co-regulated by Cyclin D and CDK4.…”
Section: Initiation Of Survivin/ Cdk4 Complex Formation In the Nucleisupporting
confidence: 74%
“…Meanwhile, Suzuki reported that Survivin could promote cell proliferation by competitively interacting with CDK4, over-expression of Survivin could release CDK inhibitors p21 (WAF1/Cip1) and p16 INK4a from CDK4. This molecular interaction may play an important role in carcinogenesis and progression of human HCC [15][16]. Therefore, detailed mechanism of LMP1 regulating Survivin in G 1 /S phase need to be further confirmed.…”
Section: Introductionmentioning
confidence: 98%
“…43 However, the mechanisms of apoptotic suppression by survivin are not completely clear. Initial observations suggested that survivin could directly suppress activation of caspase-3 44,45 ; however, more recent studies have demonstrated that survivin lacks the ability to directly inhibit caspase-3. 46,47 Other groups have proposed that survivin acts like other IAPs by binding to caspase-9 and/or by neutralizing the new IAP-inhibiting protein, Smac/Diablo, 48,49 raising the possibility that it might suppress caspases indirectly by freeing other IAP family members from the constraints of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that survivin may have an important role in the progression of HCCs. 16 Although it has been demonstrated that interference with survivin expression or function could inhibit the neoplastic growth of a wide variety of cancers, to date, there are still few reports to experimentally support this theory in HCC. 17 We reasonably postulate that survivin may be a promising and powerful target for the treatment of HCC.…”
Section: Introductionmentioning
confidence: 99%